Vespa orientalis pupae peptide hydrolysates modulate NF-κB signaling in LTA-induced pneumonia from clinical Enterococcus faecalis isolates: implications for gut microbiota - Rahman, Mujeeb Ur; Ilyas, Muhammad; Atta, Aamna; Alioui, Yamina; Ali, Sharafat; Ullah, Hidayat; Ali, Muhsin; Deng, Ting; Farooqui, Nabeel Ahmed; Ma, Renzhen; Abusidu, Mohammed; Wang, Jiayi; et al. (Frontiers in Nutrition, 2025)
IntroductionPneumonia continues to be a significant infectious disease, marked by ongoing lung inflammation, breathing difficulties, and high mortality rates, especially among young children in low-income nations.MethodsThis study explored the therapeutic potential of peptide hydrolysates from Vespa orientalis pupae in a mouse model of Enterococcus faecalis lipoteichoic acid (LTA)-induced pneumonia. Mice were administered pupae peptide hydrolysate (PPH), and outcomes were evaluated based on clinical symptoms, histopathological analysis, cytokine profiling, expression of tight junction proteins, gut microbiota analysis via 16S rRNA sequencing, and NF-κB signaling activity in the lungs.ResultsPPH treatment alleviated LTA-induced symptoms, reduced inflammation in the lungs and colon, and improved the balance of gut microbiota. It strengthens the intestinal barrier by increasing the levels of Mucin-2, Mucin-4, and tight junction proteins (Claudin-1, Occludin, ZO-1). Immune modulation was observed, with a decrease in pro-inflammatory cytokine levels, an increase in anti-inflammatory cytokine levels, and suppression of NF-κB signaling. Restoration of the gut microbiota composition further supports the therapeutic role of PPH.Discussion/conclusionThese results indicate that PPH mitigates LTA-induced pneumonia by reinforcing the intestinal barrier, modulating inflammatory pathways, including suppression of NF-κB, and restoring microbial balance. PPH represents a promising new approach for managing pneumonia as a chronic inflammatory disease.